Mutation Landscape of Homologous Recombination Repair Genes in Epithelial Ovarian Cancer in China and Its Relationship With Clinicopathlological Characteristics - Yao, Qianlan; Liu, Yanhui; Zhang, Lihua; Dong, Lin; Bao, Longlong; Bai, Qianming; Cui, Qian; Xu, Jie; Li, Min; Liu, Jing; Chuai, Shannon; Ying, Jianming; et al. (Frontiers in Oncology, 2022)
Abstract Objective: The status of homologous recombination repair (HRR) genes mutations and their impact on the survival of patients with Chinese EOC is still unclear. In this study, we retrospectively analyzed mutations of HRR genes in tumor tissues and evaluated their values for predicting survivals of Chinese EOC patients. Methods: A total of 273 primary EOC patients from five different hospitals between 2015 and 2016 were recruited. All patients received staging surgeries or debulking surgeries combined with systemic platinum-based chemotherapy. DNA was extracted from formalin-fixed, paraffin-embedded sections and analyzed for mutations using a 21-gene panel (including 13 well-known HRR genes) by next generation sequencing. Results: High grade serous carcinoma (HGSOC) accounted for 76.2% of the cohort. 34.1% (93/273) cases had 99 deleterious mutations in 9 HRR genes, including BRCA1 (56/273,20.5%), BRCA2 (20/273, 7.3%), ATM (5/273, 1.8%), RAD51C (5/273, 1.8%), RAD51D (5/273, 1.8%), BRIP1 (2/273, 1.8%), CHEK2 (2/273, 0.7%), FANCI (2/273, 0.7%), RAD54L (1/273, 0.4%). There is a strongly mutual exclusion between HRR genes. The mutation landscape revealed several unappreciated deleteriously variants in BRCA 1/2 and other HRR genes reported previously. Estimated by the mutation allele frequency, 4.8% of the patients had potential somatic HRR gene mutations, which might be underestimated. Moreover, HRR mutations mainly exist in HGSOC (83/208, 39.9%), clear cell（2/30, 6.7%）and endometroid subtype (8/20, 40%), but not seen in other rare subtypes. BRCA1 mutations tend to be present in younger patients with family history or multiple primary foci. Patients with BRCA1/2 mutations tend to have a longer progression-free survival and overall survival, while other HRR mutations carriers tend to have a shorter progression-free survival, but no significant difference in overall survival. Conclusion: This study revealed the distribution of HRR gene mutations in Chinese EOC tissues. BRCA1/2 account for the majority of HRR gene mutations and predict long prognosis in HGSOC. Non-BRCA HRR mutations also account for a very important proportion and might be associated with poor prognosis in HGSOC. It is suggested that HRR genes mutations be detected in EOC tissues, and germline status be further clarified in clinical algorithm for potential targeted therapy, genetic screening and prognosis prediction.